Coming to terms with the conflict in and about northern Ireland: Lessons from the healing through remembering project - Hamber Brandon (Temida, 2004)
In Northern Ireland the debate about what strategies to use to deal with the conflict is gaining momentum. Questions about truth, justice, compensation and more recently of reconciliation are common place. Recently, there have been several calls for a South African-style truth commission. One danger however, is that the strategies adopted to deal with the past, such as a truth commission, may flow directly from the political negotiation process with little civil society input. This is one of the reasons why the Healing Through Remembering Project was launched in early October 2001. The Project made up of a diverse group of people from all political backgrounds and from different communities, sought to identify and document possible mechanisms and realizable options for how remembering should occur so that healing could take place. The project undertook a consultation process posing the question: "How should we remember the events connected with the conflict in and about Northern Ireland". The project received a wide range of submissions. It used these to develop a series of recommendations. These included the need for acknowledgement leading to truth recovery storytelling, a Day of Reflection, a permanent living memorial museum and network of commemoration and remembering projects.